Modeling the formation and growth of atmospheric molecular clusters: A review. (November 2020) - Elm, Jonas; Kubečka, Jakub; Besel, Vitus; Jääskeläinen, Matias J.; Halonen, Roope; Kurtén, Theo; Vehkamäki, Hanna
Abstract: Molecular clusters are ubiquitous constituents of the ambient atmosphere, that can grow into larger sizes forming new aerosol particles. The formation and growth of small clusters into aerosol particles remain one of the largest uncertainties in global climate predictions. This has made the modeling of atmospheric molecular clustering into an active field of research, yielding direct molecular level information about the formation mechanism. We review the present state-of-the-art quantum chemical methods and cluster distribution dynamics models that are applied to study the formation and growth of atmospheric molecular clusters. We outline the current challenges in applying theoretical methods and the future directions to move the field forward. Highlights: Quantum chemical methods applied to cluster formation are reviewed. A detailed overview of the progress in cluster formation studies. Further prospects in the field.